Population density, geographical distribution and habitat of Talaud bear cuscus (Ailurops melanotis Thomas, 1898) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Repi T, Masy’ud B, Mustari AH, Prasetyo LB. 2020. Population density, geographical distribution and habitat of Talaud bear cuscus (Ailurops melanotis Thomas, 1898). Biodiversitas 21: 5621-5631. The Talaud bear cuscus (Ailurops melanotis) has been reported from Sangihe (the largest island in the Sangihe Island group) and Salibabu (within the Talaud Islands). As an endemic species of Indonesia, this species is rare and there is no certainty regarding its precise geographic distribution or population size. This research aimed to estimate population density and provide the first preliminary data on its geographical distribution, as well as general description of its habitat. Our research shows that A. melanotis occurs on three islands: Salibabu Island, Nusa Island, and Bukide Island, and probably also exists in the Sahandaruman mountain on Sangihe Island. Our population surveys estimate, population density on each island as: Salibabu: 3.69 ± 2.54 ind/km2, with an estimated total population of 28.95 individuals, Nusa Island: was 12.31 ± 2.58 ind/km2, with an estimated population of 19.08 individuals, and Bukide Island: 7.17 ± 1.79/km2, with an estimated population of 10.40 individuals. Information regarding population is a key guiding factor in conservation efforts, where population size is related to extinction risk (threat status) and its geographical distribution, this can help to determine conservation priorities for species or habitats.
Keywords: Ailurops melanotis, distribution, conservation, habitat, density, population